Planktonic diatom community dynamics in a tropical flood-pulse lake: the Tonle Sap (Cambodia). Issue 1 (2nd January 2019) - Tudesque, Loïc; Pool, Thomas K.; Chevalier, Mathieu
Abstract : It has been proposed that, within flood-pulse systems, seasonally dynamic conditions promote extremely high levels of biodiversity. In this paper, we aim to understand how variation in environmental conditions and habitat availability, across space and time, influences the structure and composition of plankton diatom communities within the Tonle-Sap Lake (Cambodia) during two flood-pulse cycles. We hypothesize that (i) communities vary considerably across space and time, (ii) environmental filtering accounts for a substantial portion of the variation in community composition, and (iii) shifts in meta-community structure occur seasonally, due to variation in both environmental conditions and habitat availability. A principal component analysis and a permutational multivariate analysis of variance were used to characterize spatio-temporal variations in environmental conditions, community structure and composition. Determinants of community variations across space were identified by redundancy analyses and variation partitioning, while seasonal changes in meta-community structure were assessed by investigating temporal changes in β-diversity. Our results indicate that (i) spatial variations in community structure and composition are largely influenced by the seasonal flood-pulse, (ii) environmental filtering is the most likely process driving the compositional changes, and (iii) changes in diatom life-form community provide insights into the hydrological functioning of the Tonle Sap. We conclude that the survey of diatom communities may constitute a relevant sensor of hydrological change in the system and could be used to derive regionally specific hypotheses about how global climate change is impacting the lake's functioning.